Prototype Smart Baby’s Room Berbasis Iot Di PT Ozami Inti Synergy Untuk Orang Tua Sibuk - Maren, Wilson Christopher Fisteos; Ismail, Harries Arizonia; Yusup, Yusup (INTECOMS: Journal of Information Technology and Computer Science, 2024)
This research aims to design and develop a prototype of the Smart Baby's Room based on the Internet of Things (IoT) at PT Ozami Inti Synergy,as a solution for busy parents. This tool is designed to monitor baby's condition and surrounding environment in real-time through a mobile application. Key features include monitoring temperature, humidity, air quality, as well as sound and motion detection of the baby. Data from these sensors is transmitted to an IoT platform, allowing parents to receive notifications and remotely monitor the conditions remotely. This implementation is expected to improve baby's safety and comfort, as well as providing peace of mind for parents who cannot always be at home. parents who cannot always be at home. This prototype was tested to ensure its reliability and effectiveness in a controlled environment.